Decreased miR-497-5p Suppresses IL-6 Induced Atrophy in Muscle Cells - Paula P. Freire; Sarah S. Cury; Letícia O. Lopes; Geysson J. Fernandez; Jianming Liu; Leonardo Nazario de Moraes; Grasieli de Oliveira; Jakeline S. Oliveira; Diogo de Moraes; Otavio Cabral-Marques; Maeli Dal-Pai-Silva; Xiaoyun Hu; et al. (Cells, 2021)
Interleukin-6 (IL-6) is a pro-inflammatory cytokine associated with skeletal muscle wasting in cancer cachexia. The control of gene expression by microRNAs (miRNAs) in muscle wasting involves the regulation of thousands of target transcripts. However, the miRNA-target networks associated with IL6-induced muscle atrophy remain to be characterized. Here, we show that IL-6 promotes the atrophy of C2C12 myotubes and changes the expression of 20 miRNAs (5 up-regulated and 15 down-regulated). Gene Ontology analysis of predicted miRNAs targets revealed post-transcriptional regulation of genes involved in cell differentiation, apoptosis, migration, and catabolic processes. Next, we performed a meta-analysis of miRNA-published data that identified miR-497-5p, a down-regulated miRNAs induced by IL-6, also down-regulated in other muscle-wasting conditions. We used miR-497-5p mimics and inhibitors to explore the function of miR-497-5p in C2C12 myoblasts and myotubes. We found that miR-497-5p can regulate the expression of the cell cycle genes CcnD2 and CcnE1 without affecting the rate of myoblast cellular proliferation. Notably, miR-497-5p mimics induced myotube atrophy and reduced Insr expression. Treatment with miR-497-5p inhibitors did not change the diameter of the myotubes but increased the expression of its target genes Insr and Igf1r. These genes are known to regulate skeletal muscle regeneration and hypertrophy via insulin-like growth factor pathway and were up-regulated in cachectic muscle samples. Our miRNA-regulated network analysis revealed a potential role for miR-497-5p during IL6-induced muscle cell atrophy and suggests that miR-497-5p is likely involved in a compensatory mechanism of muscle atrophy in response to IL-6.